Athlete monitoring in elite sport - Neupert, E. (University of Winchester, 2021)
Purpose: Athlete monitoring systems (AMS) are employed widely in elite sport. Despite this, difficulties in executing research within elite sporting organisations means that the typical AMS practices and the value end-users place in their AMS remains under-reported. A range of methodological and implementation issues for AMS have been previously described e.g. poor stakeholder buy-in. This is concerning, because if an AMS fails to be effective, poor athletic performance or maladaptation may occur. Therefore, elucidating current monitoring practices within elite sport and providing guidance to address any implementation issues encountered has the potential to provide a significant contribution to research within this area. Aim: To explore athlete monitoring practices in elite sport and the utility of a behavioural change intervention to improve buy-in to monitoring. Methods: A survey was used to gather the opinions of elite sport practitioners on their AMS, and semi-structured interviews captured athlete and coach AMS perceptions. A behaviour change intervention, which aimed to improve the engagement of elite athletes with their AMS, was assessed for its utility. Results: For the first time, this study was able to reveal the extent of AMS customisation across a range of elite sports. Consequences of this approach included: significant subjective-questionnaire variability, reduced scientific methodological rigour, limited -practitioner confidence in their data and difficulty discerning meaningful change within it. AMS adherence was not found to be enhanced by a formalised behavioural change intervention. Conclusion: Customisation of athlete monitoring metrics has reduced the scientific rigour of AMS. Further, the fast changing landscape in elite sport makes it challenging to apply a behaviour change intervention to modify AMS adherence. In an effort to resolve these AMS implementation issues, a series of recommendations for the applied practitioner working with AMS were compiled, thus providing an original contribution to knowledge in both applied practice and research.